Atypical Presentations of IPEX: Expect the Unexpected - Consonni, Filippo; Ciullini Mannurita, Sara; Gambineri, Eleonora (Frontiers in Pediatrics, 2021)
Immune dysregulation, polyendocrinopathy, and enteropathy, X-linked (IPEX) syndrome is a rare disorder that has become a model of monogenic autoimmunity. IPEX is caused by mutations in FOXP3 gene, a master regulator of regulatory T cells (Treg). Cases reported in the last twenty years demonstrate that IPEX clinical spectrum encompasses more than the classical triad of early-onset intractable diarrhea, type 1 diabetes (T1D) and eczema. Atypical cases of IPEX include patients with late-onset of symptoms, single-organ involvement, mild disease phenotypes or rare clinical features (e.g., atrophic gastritis, interstitial lung disease, nephropathy etc,). Several atypical presentations have recently been reported, suggesting that IPEX incidence might be underestimated. Immunosuppression (IS) treatment strategies can control the disease, however at the moment allogenic hematopoietic stem cell transplantation (HSCT) is the only available definitive cure, therefore it is important to achieve a prompt diagnosis. This review aims to describe unusual clinical phenotypes, beyond classical IPEX. Overall, our analysis contributes to increase awareness and finally improve diagnosis and treatment intervention in IPEX in order to ensure a good quality of life.